Tetralogy of Fallot Will be Treated Interventionally Within Two Decades - Muhammed Riyas K. Rahmath (14155899) (2020)
Tetralogy of Fallot is considered a prototype congenital heart disease because of its embryological, anatomical, pathophysiological, and management aspects. Current management usually relies on a complete surgical repair that is electively performed between 3 and 6 months of age. With the advances of interventional cardiology especially in the fields of ventricular septal defect closure, stent, and pulmonary valve replacement, the question of complete repair of tetralogy of Fallot by interventional means can be discussed. Tetralogy of Fallot is a complex disease with multiple lesions, all individually amenable to transcatheter treatment. In this article, we will review current status of various aspects of tetralogy of Fallot focusing on interventional aspects, giving insights of what would be the ideal platform of a fully interventional repair. Other Information Published in: Pediatric Cardiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00246-020-02297-z